Revisiting Plant Biostimulants - Singh Meena, Vijay; Prasad Parewa, Hanuman; Kumari Meena, Sunita (IntechOpen, 2022)
Revisiting Plant Biostimulants focuses on recent advances in plant biostimulants (PBs), an eco-friendly sustainable technology that supports the increased agricultural production required to feed rapidly growing populations. PBs contain diverse bioactive natural substances: (i) humic and fulvic acids, (ii) animal and vegetal protein hydrolysates, (iii) macroalgae seaweed extracts, and (iv) silicon, as well as beneficial microorganisms. There are many concerns about the sustainability of current conventional methods as continued use of chemicals degrades both soil and the environment. This book explores the use of PBs, and their potential responses to current and impending environmental change.